A.3 A novel recessive TNNT1 congenital core-rod myopathy in French Canadians. (June 2022) - Pellerin, D; Aykanat, A; Ellezam, B; Troiano, EC; Karamchandani, J; Dicaire, M; Petitclerc, M; Robertson, R; Allard-Chamard, X; Brunet, D; Konersman, CG; Mathieu, J; et al.
Abstract : Background: Mutations in the slow skeletal muscle troponin T ( TNNT1 ) gene cause a congenital nemaline myopathy resulting in death from respiratory insufficiency in early infancy. We report on four French Canadians with a novel congenital TNNT1 myopathy. Methods: Patients underwent lower extremity and paraspinal MRI, quadriceps biopsy and genetic testing. TNNT1 expression in muscle was assessed by quantitative PCR and immunoblotting. Wild type or mutated TNNT1 mRNAs were co-injected with morpholinos in a zebrafish knockdown model to assess for rescue of the morphant phenotype. Results: Four patients shared a novel missense homozygous mutation in TNNT1 . They developed from childhood slowly progressive limb-girdle weakness with spinal rigidity and contractures. They suffered from restrictive lung disease and recurrent episodes of rhabdomyolysis. Older patients remained ambulatory into their sixties. Lower extremity MRI showed symmetrical myopathic changes. Paraspinal MRI showed diffuse fibro-fatty involution. Biopsies showed multi-minicores. Nemaline rods were seen in half the patients. TNNT1 mRNA expression was similar in controls and patients, while levels of TNNT1 protein were reduced in patients. Wild type TNNT1 mRNA rescued the zebrafish morphants but mutant transcripts failed to do so. Conclusions: This study expands the spectrum of TNNT1 -related myopathy to include a milder clinical phenotype caused by a functionally-confirmed novel mutation.